(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Nephritic syndrome is a symptom complex that develops against the background of inflammatory kidney diseases. The syndrome is characterized by the appearance of red blood cells in the urine, protein, increased blood pressure and the formation of peripheral edema of soft tissues. Nephritic syndrome is one of the syndromes that indicates the presence of glomerulonephritis in humans .